Zgodovinski razvoj pojma javnih služb in storitve splošnega gospodarskega pomena v pravu EU – javne službe med konkurenčnostjo in solidarnostjo - Dobelšek, Anže (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
The new European legal regulation has a major impact on the regulation of services of general economic interest (SGEI). From the current public service legal regime, it has focused primarily on the legal regime for the granting of special or exclusive rights for the exercise of these activities, leaving aside the current regulation of the legal and organisational forms of the providers of these services in national legislation and setting only the conditions that these operators must meet for the direct acquisition of special or exclusive rights to carry out these activities. It also provides for a uniform regulation of the foundations of a competitive procedure for the granting of special or exclusive rights for the implementation of SGEIs, which are the basis for regulating this procedure in national legislation. The set of novelties, in its essence, represents a new legal regime that has eliminated many years of defective regulation in this area, particularly in relation to the rules of European competition law.
Keywords: Evropska unija; gospodarske javne službe; gospodarsko poslovanje; javne službe; konkurenčno pravo; konkurenčnost; pravna ureditev; zakonodaja; zgodovinski pregledi